PENGEMBANGAN BUKU AJAR MIKROBIOLOGI BERBASIS HASIL PENELITIAN EKSPLORASI DAN KARAKTERISASI BAKTERI PADA MAKANAN DAN MINUMAN - Qomariyah, Ismi Nurul; Prayitno, Trio Ageng (Jurnal Pendidikan Biologi, 2018)
Students need microbiology textbooks that contain the latest research results so that microbiological material is dynamic. The research problem is how is the form of developing microbiology textbooks based on research results that meet the criteria of eligibility or validity. The study aims to determine the form of development of microbiology textbooks based on research results that meet the criteria of eligibility or validity. This research is a development research using the Thiagarajan 4-D development model, which includes define, design and develop stages. The microbiology textbooks developed were tested for validity and attractiveness to microbiology material experts, instructional media experts, practitioners and a small group of students who had taken microbiology courses. The results showed that the research-based microbiology textbooks were declared feasible or valid by a team of experts, practitioners, and students. Research-based microbiology textbooks are unique in that they contain research work procedures in the laboratory so as to facilitate students to understand microbiology material and establish life skills.